Dioxins and dioxin-like compounds in meat and meat products - E. Aoudeh; E. Oz; M. R. Khan; F. Oz (Теория и практика переработки мяса, 2022)
Dioxin and dioxin-like compounds are persistent organic pollutants that received considerable attention in recent years due to their high potential toxicity, wide distribution and extreme stability. Polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) mainly occur in the environment as a result of several human activities including combustion, incineration and many other industrial activities, whereas polychlorinated biphenyls (PCBs) congeners were intentionally manufactured and widely used in various fields. Since dioxin and dioxin-like compounds are found in various environmental compartments (air, water, soil, sludge, sediment, food, feed, blood, animal and human tissues), humans could be exposed to them via inhalation, dermal contact or food ingestion. However, 90% of human exposure to dioxin is through food ingestion particularly foods from animals and foods that are rich in fat. In contrast, only low levels have been found in food items of plant origin. Exposure to dioxin compounds is associated with various adverse health problems. However, their toxicity varies dramatically according to the type of dioxin, species of exposed organism, as well as exposure frequency and duration. Dioxins are mainly determined by instrumental chromatographic methods such as GC-HRMS and GC–MS/MS. Many efforts have been made to remove, reduce and prevent these hazardous substances from the environment. However, the best method for reducing human exposure to dioxins and dioxin-like compounds is controlling and minimizing their production. In this article, structures, sources, exposure, toxicity and analysis methods of dioxin and dioxin-like compounds in meat and other foods were reviewed.